2014
DOI: 10.1186/s12967-014-0282-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of 25 genotypes of human papillomaviruses for their physical statuses in cervical precancerous/cancerous lesions: a comparison of E2/E6E7 ratio-based vs. multiple E1-L1/E6E7 ratio-based detection techniques

Abstract: BackgroundCervical lesions caused by integrated human papillomavirus (HPV) infection are highly dangerous because they can quickly develop into invasive cancers. However, clinicians are currently hampered by the lack of a quick, convenient and precise technique to detect integrated/mixed infections of various genotypes of HPVs in the cervix. This study aimed to develop a practical tool to determine the physical status of different HPVs and evaluate its clinical significance.MethodsThe target population compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This issue has already been proven in Cervical Cancer [40]. One of the limitations in our study was to use E2 / E6 ratio for determination of physical status of HPV genome while Zhang et al have demonstrated that E2/E6 or E2/E7 is less sensitive and predictive than E2/E6E7 for determination of physical status of HPV genome in cervical cancer [54]. Therefore, in our study, the percentage of integrated HPV genomes was probably more than the percentage we reported.…”
Section: Discussionmentioning
confidence: 85%
“…This issue has already been proven in Cervical Cancer [40]. One of the limitations in our study was to use E2 / E6 ratio for determination of physical status of HPV genome while Zhang et al have demonstrated that E2/E6 or E2/E7 is less sensitive and predictive than E2/E6E7 for determination of physical status of HPV genome in cervical cancer [54]. Therefore, in our study, the percentage of integrated HPV genomes was probably more than the percentage we reported.…”
Section: Discussionmentioning
confidence: 85%
“…[ 36 ] Some experts have hypothesized that HPV16 has better evolutionary ability to escape the effects of immune surveillance, while non-HPV16 genotypes are often better controlled by the immune response. [ 36 , 37 ] Consequently, in women with progressive weakening of the immune system, the immune control over non-HPV16 types may be lost, promoting the rise in the prevalence of types frequently targeted by a competent immune system. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 , 37 ] Consequently, in women with progressive weakening of the immune system, the immune control over non-HPV16 types may be lost, promoting the rise in the prevalence of types frequently targeted by a competent immune system. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated in numerous studies that HPV16 shows a different integration pattern in conjunction with disease. Zhang et al [33] found a 27.7% integration rate of HPV16 in precancerous lesions. This study detected a high number of samples with fully integrated HPV16 in normal samples (2/6, 33%), similar to a finding reported by Dutta et al [34] (27% integration in normal samples).…”
Section: Discussionmentioning
confidence: 99%